Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

The evolution of land governance in Myanmar: A historical analysis of the people-land nexus in the Konbaung dynasty and British colonial eras - Phyu Phyu Han; Win Min Paing; Masahiko Ota; Takahiro Fujiwara (Forest Policy and Economics, 2025)

Epidemiological and clinical profile of snake envenomation in children and adolescents admitted to tertiary hospitals in Yangon, Myanmar - Khin Than Yee; Kyaw Zin Wai; Aung Pyae Phyo; Lai Lai San; Khin Moe Latt; Tin Tin Htike; Thet Htet Aung; Aung Myat; Han Win; Zaw Myint; Zaw Than Htun (Toxicon, 2024)

Adavosertib-encapsulated metal-organic frameworks for p53-mutated gallbladder cancer treatment via synthetic lethality - Shijie Li; Sarun Juengpanich; Win Topatana; Tianao Xie; Lidan Hou; Yiyuan Zhu; Jiadong Chen; Yukai Shan; Yina Han; Ziyi Lu; Tianen Chen; Charlie Topatana; et al. (Science Bulletin, 2024)

The state-private hybrid forest policy in Myanmar: The impact of neoliberalism on the forestry sector after the 1990s - Win Min Paing; Phyu Phyu Han; Masahiko Ota; Takahiro Fujiwara (Forest Policy and Economics, 2023)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Two new pyrrolo-2-aminoimidazoles from a Myanmarese marine sponge, Clathria prolifera - So-Yeun Woo; Nwet Nwet Win; Chin Piow Wong; Takuya Ito; Shotaro Hoshino; Hla Ngwe; Aung Aung Aye; Nang Mya Han; Huiping Zhang; Fumiaki Hayashi; Ikuro Abe; Hiroyuki Morita (Journal of Natural Medicines, 2018)

Effects of 1-methylcyclopropene (1-MCP) and polyethylene (PE) film liner treatments on the fruit quality of cold-stored ‘Gamhong’ apples - Kyoung-ook Kim; Jingi Yoo; Jinwook Lee; Nay Myo Win; Seulgi Ryu; Jeung-Sul Han; Hee-Young Jung; Myoung-Gun Choung; Yong-Deuk Kwon; Dong Hoon Lee; In-Kyu Kang (Horticulture, Environment, and Biotechnology, 2018)

Seasonal dynamics influencing coastal primary production and phytoplankton communities along the southern Myanmar coast - Maung-Saw-Htoo-Thaw; Shizuka Ohara; Kazumi Matsuoka; Tatsuya Yurimoto; Shota Higo; Khin-Ko-Lay; Win-Kyaing; Myint-Shwe; Sein-Thaung; Yin-Yin-Htay; Nang-Mya-Han; Khin-Maung-Cho; et al. (Journal of Oceanography, 2017)

Biological and cytoselective anticancer properties of copper(II)-polypyridyl complexes modulated by auxiliary methylated glycine ligand - Hoi-Ling Seng; Wai-San Wang; Siew-Ming Kong; Han-Kiat Alan Ong; Yip-Foo Win; Raja Noor Zaliha Raja Abd. Rahman; Makoto Chikira; Weng-Kee Leong; Munirah Ahmad; Alan Soo-Beng Khoo; Chew-Hee Ng (BioMetals, 2012)